Preliminary results about the use of injected Lysozime (LIZOVET) to improve the response to synchronization protocol for insemination in buffalo heifers - Francisco Javier Vargas Ortiz; Johnny Ronnel Bracho Ylarraza (Revista Científica)
Lysozyme is a natural enzyme present in many body fluids in animals and humans, where it fulfills immunostimulant, bactericidal, virucidal, and anti-inflammatory functions. A commercial product based on Lysozyme (LIZOVET, Laboratory Agriquimvet, Aragua State, Venezuela) for use in different animal species has effectively increased production and health in cattle, poultry, and pigs. However, the effect of Lysozyme on buffalo reproduction is little known. The objective of this work was to determine the effect of injectable Lysozime (Lizovet) over the response to synchronization protocol for insemination in buffalo heifers. We conducted small field trials in buffalo farms in Barinas state, Venezuela. A group of 20 heifers was prepared 21 days before to apply a synchronization protocol for insemination at the beginning of the reproductive season with a complete mineral mix. Additionally, a treatment group (n=10) received treatment with injectable Lysozyme at a dose of 1 cc/60 Kg of intramuscular weight weekly for three weeks. The other heifers were not treated and were left as a control group (n=10). Preliminary results in this study showed that in the case of heifers, 100% of the group treated with LIZOVET were classified as suitable for admission to the insemination program by presenting ovarian follicles with an average size greater than 11 mm and the presence of corpus luteum, compared to the control group where only 30% of them classified for insemination by showing an average size of ovarian follicles of 7.5 mm. In conclusion, Lysozyme (LIZOVET) effectively improved the response to synchronization protocol for insemination in buffalo heifers. Future expectations are probable by favoring follicular growth at the ovarian level. The latest deserves further studies.